SPECIFICITY OF RESEARCH OF SPIRITUAL HERITAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article widely reflects the concept of spiritual heritage and its definition, the uniqueness of its research, as well as the great heritage of the Kyrgyz people within the framework of the Manas epic, the spiritual values of our people. Also, when the author studied the concept of spiritual heritage, its specific role in the historical development of ethnic groups, nations and races was noted. In fact, the article clarifies the close connection between the concepts of spiritual heritage and ideology, which is of greatest interest for our research. First, the concept of “spiritual heritage” was analyzed, and then its features were determined. In addition, the article describes in detail the values and heritage of the Kyrgyz people, preserved from ancient times after independence.
Keywords: spiritual heritage, ideology, ethnic value, epic “Manas”, ethnic ideology.